Are Old Dogs Who Undergo Total Hip Replacement More Predisposed to Perioperative Femoral Fractures than Young Dogs? - Jacot, Valentine (Veterinary Evidence, 2016)
Clinical bottom line There is currently insufficient evidence that old dogs undergoing total hip replacement are more predisposed to perioperative femoral fractures in comparison to young dogs.